(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: A young dental patient is especially vulnerable during childhood and adolescence, on account of different cognitional prerequisites and developmental processes, intellectual as well as physical, as compared to adults. Objectives: To explore children’s and adolescents’ experiences of general, oral and dental treatment pain and to gain insight into the knowledge and attitudes of dentists towards pain management. Materials and Methods: The responses of 390 children and adolescents (8-19year olds) on the 40 items CPI were examined. Most commonly experienced CPI pain situations were analysed by Exploratory Factor Analysis to reduce the length of the questionnaire. 190 kids with disability (12-18-year-olds) and their matched controls were studied for DDQ. 390 dentists were evaluated for their knowledge of pain management and attitude. Results: About 50% of the children and adolescents experiencing invasive dental procedures like ‘Dental injection’, ‘Tooth drilling’ or ‘Tooth extraction’, had experienced them as painful. The pain intensity experience was multiplied by having higher dental anxiety, a disability, age less than 14 years old, or gender (female). The disabled children and adolescents had significantly higher DDQ scores as compared to controls, despite similar dental health in both the groups. Dentists with more professional experience and/or female dentists applied better pain management approach. Conclusion: Kids with or without a disability and the one with higher dental anxiety must be recognised as more vulnerable to pain. Such patients should be offered extra care and also pain relief during invasive dental treatments. Dentists should ensure all children a pain-free dental treatment.